ANALISIS ANTRIAN ANGKUTAN PENYEBERANGAN PELABUHAN MERAK - Ariyo Kurniawan; Sugito Sugito; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Marine transportation has an important role on economy and migration from one island to another island. Port is a gateway to enter an area and connecting infrastructure between islands. Merak port as the connector of traffic lanes between Java’s island and Sumatra’s island with Ro-Ro ship. Ro-Ro ship is marine transportation that can load a vehicle rolling on and rolling off the ship with its auto-movement (Roll on Roll off). As a service provider of the Ro-Ro ships, the port of Merak trying to serve Ro-Ro ship as good as possible. Measurement of performance system can be analyzed with direct research in the port. The research is being done by observation and recording of the Ro-Ro ships at the pier port of Merak. Based on the results of the analysis, queue model at the port of Merak is (G/G/5) :(GD/∞/∞). Queuing system simulation and ship docking’s cost analysis can be a reference for the port in optimizing management performance the port of Merak crossing. Keywords: supplemental cost, defined benefit plans, accrued benefit cost.